Pengaruh Kinerja Keuangan Untuk Menilai Likuiditas Saham Pada Perusahaan Yang Terdaftar Di Index Saham Syariah Indonesia (Issi) - Nasrun Ritonga; Widia Wardani (Jurnal Manajemen Akuntansi (JUMSI), 2021)
One factor that influences a company's liquidity is financial performance in the company. In this study, the author uses companies listed on the Indonesian Sharia Stock Index (ISSI), during 2014-2016. The number of companies used in this study is 169 companies, the total number of data used in this study was 507 data. This study used thee company's financial performance as an independent variable, with indicators of current ratio, return on assets, leverage, activity, and earnings per share, which would be seen to influence the stock liquidity variable as the dependent variable, with an indicator of the volume of stock trading transactions during the 2014-2016 study period.  Based on the results of the t statistic test, the Variable Liquidity Ratio (CR) had a significant influence on stock liquidity with a p-value (0.019). Profitability (ROA) has a significant effect on stock liquidity with p-value (0.049). Leverage variable had a significant negative effect on stock liquidity with p-value (0.022). Activity Ratios had  significant effect on stock liquidity with p-value (0.004). Market Ratio (EPS) which had a significant influence on stock liquidity with a p-value (0.025).